Analisis Pelaksanaan Sensus Harian Rawat Inap di RSUD Dr. Saiful Anwar Malang - Ferly Ferly; Rossalina Adi Wijayanti; Novita Nuraini (Politeknik Negeri Jember, 2020)
Abstract Information obtained from the daily inpatient census in the form of data that will be processed into information needed by the hospital, so that the daily inpatient census activities must be carried out correctly in accordance with procedures so that the data generated is accurate and can be used as a basis for decision making for management. This study aims to analyze the factors causing the inactivity of inpatient daily census activities correctly using a fishbone diagram. This research is a qualitative descriptive study conducted at Dr. Saiful Anwar Malang in February - March 2020. The subjects of this study were the daily census officer of the inpatient room, and the daily census officer of the medical record section. Data was taken by interview and observation methods. Data were analyzed using fishbone diagrams. The results of this study indicate that the factors that cause the inability of the inpatient daily census to be conducted correctly are Man (misperception of the inpatient census daily officer between the understanding day of care with the length of stay, educational background of the officer not from the medical record, and the officer has never attended training on the census), Money (there is no funding budget for training implementation, Materials (census information system on billing system is not implemented, census recapitulation is still manual using paper forms and Microsoft excel), Method (Daily SOP for inpatient census has not been revised), Machine (census application on billing system is not implemented) Fishbone diagrams where the in-patient census daily activities are carried out correctly are mostly caused by Man factors and Materials factors.